Pelatihan Pembelajaran Bahasa Indonesia Berbasis Media Visual SDN 5 Karang Anyar - Muhammad Singgih; Riska Aprilliya (Al Mufid, 2023)
Visual media can facilitate the achievement of goals to understand and remember the information or messages contained in the image. The situation and problems that occur with partners, it is known that the problem at SDN 5 Karang Anyar Lampung Selatan is that it does not support the facilities owned by the school, thus making the lack of competence possessed by teachers in the use of learning media. The result of this service activity is an increase in student competence, especially Indonesian learning, and create a learning atmosphere that is focused on the material presented. The spirit of learning seen in the learning process is a sign of the success of the community service activity process.